2018
DOI: 10.1002/ppul.24138
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient initiation of long‐term continuous positive airway pressure in children

Abstract: Initiating CPAP in an outpatient setting in children is feasible and effective in selected subjects. A high rate of compliance can be achieved as well as a correction of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…All pts were started on ventilation as in‐pts, most of them (83%) in the general pediatric ward. Two groups have published outpatient long‐term ventilation initiation experience and compared them to in patient experience with promising results 25,26 . As stated before, lack of bed availability for family NIV training explains the delay in ventilation start.…”
Section: Discussionmentioning
confidence: 99%
“…All pts were started on ventilation as in‐pts, most of them (83%) in the general pediatric ward. Two groups have published outpatient long‐term ventilation initiation experience and compared them to in patient experience with promising results 25,26 . As stated before, lack of bed availability for family NIV training explains the delay in ventilation start.…”
Section: Discussionmentioning
confidence: 99%
“…CPAP was changed for NIV in case of persistent oxygen desaturations and/or hypercapnia despite the highest tolerated CPAP pressure and/or in case of nocturnal hypoventilation without respiratory events (Kushida et al, ). CPAP/NIV initiation was performed within a specific therapeutic education program adjusted on mental age, cognition, and cooperation (Amaddeo et al, ). The therapeutic education tools integrated booklets, a teddy bear breathing with NIV, and playful evaluation tools (see http://vnietsommeil.aphp.fr).…”
Section: Methodsmentioning
confidence: 99%
“…CPAP was use was better if another family member was also on CPAP, obesity did not affect CPAP adherence ( 41 ). Amaddeo et al ( 42 ) studied out-patient initiation of CPAP therapy in children and showed a general high level of adherence in their cohort of 31 children (3 were obese).…”
Section: Cpap In Obese Childrenmentioning
confidence: 99%